CONSUMER PERCEPTION AND BRAND LOYALTY TOWARDS OVER THE COUNTER BRAND MEDICINES OF MAJOR PHARMACEUTICALS COMPANIES WITH SPECIAL REFERENCE TO RAJASTHAN - Dadhich, Abhishek; Dixit, Kavaldeep (International Journal of Engineering Technologies and Management Research, 2017)
The study intends to explore the consumer perception towards over-the-counter (OTC) medicines and factors that influence consumer buying behavior for OTC brand medicines marketed by pharmaceutical companies. It also aims to study the impact of marketing mix factors on consumer perception and OTC brand loyalty. The research is descriptive in nature. It is based on primary data which is collected via structured questionnaire. The hundred respondents were participated in pilot study to understand and validate the questionnaire. The primary data obtained are analysed to identify the consumer perception and OTC brand loyalty promoted by the pharmaceutical companies. The study was conducted in period of 1 December 2016 to 31 March 2017. The respondents are from different districts of Rajasthan. 411 respondents participated on simple convenient non-probability sampling basis. In the study the dependent variables like consumer perception and brand loyalty with independent variables like consumer self-medication and OTC marketing mix factors are considered. It is observed in present study that OTC marketing mix factors like Place, Price and Promotion has positive impact on consumer perception and OTC brand loyalty whereas self-medication practices have negative impact. The study also revealed that Place (Product availability), Price and Promotions are the major influencing factor in considering consumer OTC medicine buying behavior.